Durability investigation and performance study of hydrothermal synthesized platinum-multi walled carbon nanotube nanocomposite catalyst for proton exchange membrane fuel cell. (1st November 2017) - Mirzaei, Farokh; Parnian, Mohammad Javad; Rowshanzamir, Soosan
Abstract: In this work, a highly dispersed Pt nanoparticles on multi-walled carbon nanotubes catalyst was prepared by hydrothermal method. The synthesized Pt/MWCNT nanocomposite electrocatalyst was characterized using XRD, XRF, FESEM, TEM, and EDX. In the first step, the electrochemical activity and stability of the Pt/MWCNT and Pt/C catalysts were investigated in half cell condition using cyclic voltammetry for 4000 cycles. The Pt/C catalyst showed no activity after 2000 potential cycles, conversely, the Pt/MWCNT catalyst was more active after a potential cycling of 4000 cycles. The cyclic voltammetry results of the first, 1000th, 2000th, 3000th, and 4000th cycle for synthesized Pt/MWCNTs and commercial Pt/C catalysts showed the Pt/MWCNTs was more stable. Then, the membrane electrode assemblies (MEAs) were fabricated for each catalyst. The accelerated durability test (ADT) was done for the MEAs in the high potential operation in the fuel cell test station. The morphology of the fabricated MEAs was determined by FESEM before and after the accelerated degradation test. The polarization test, impedance, and cyclic voltammetry results for MEAs before and after degradation test in fuel cell test station were reported and the results showed the synthesized Pt/MWCNT is more stable catalyst than commercial Pt/C. Graphical abstract: Highlights: A hydrothermal method was employed to prepare Pt/MWCNT electrocatalyst. The electrochemical activity of the Pt/MWCNT and Pt/C electrocatalysts were investigated. The stability of the Pt/MWCNT and Pt/C electrocatalysts were investigated. The Pt/MWCNT catalyst showed better durability after a potential cycling of 4000 cycles. Membrane electrode assemblies were fabricated and accelerated durability tests were done.